A rapid review and synthesis of the effectiveness of programmes initiating community-based antiretroviral therapy in sub-Saharan Africa - Raymond Chimatira; Andrew Ross (AOSIS, 2020)
Background: Community-based antiretroviral therapy initiation (CB-ARTi) has the potential to reduce attrition by increasing access to care, reducing patient costs, decongesting clinics and ensuring improved uptake of ART. There is a paucity of research that identifies successful implementation of CB-ARTi in sub-Saharan Africa (SSA). Objectives: The aim of the study was to review and describe the evidence on the effectiveness of CB-ARTi programmes that start ART in communities in comparison with the current standards of care in SSA. Methods: A rapid review of grey and published peer-reviewed literature between January 2009 and July 2019, by using PubMed, PDQ-Evidence, Google Scholar, clinical trial databases and major HIV (human immunodeficiency virus) conference websites, was conducted. Search terms used included 'community-based', 'home initiation community models', 'antiretroviral therapy', 'clinical outcomes', 'viral suppression', 'retention in care', 'loss to follow-up', 'HIV' and 'sub-Saharan Africa'. Results: The search yielded 90 articles and reports following the removal of duplicates. After initial screening and full-text screening, six articles remained and were included in the qualitative narrative synthesis. This included four randomised control trials and two cohort studies of specific interventions comparing CB-ARTi with the standard of care in SSA. There is evidence that CB-ARTi can increase access to HIV-testing services, linkage to ART, retention in care and viral suppression rates and is possibly not inferior to facility-based healthcare. Conclusion: CB-ARTi has the potential to increase access to HIV services to people living with HIV in SSA. The results mentioned previously suggest that CB-ARTi models could prove to be equal and possibly not inferior to facility-based ones and warrant further investigation.